2010
DOI: 10.1007/s11632-010-0005-6
|View full text |Cite
|
Sign up to set email alerts
|

Cellulase in Anoplophora glabripennis adults fed on original host tree species and non-original host trees

Abstract: Cellulase activities of Anoplophora glabripennis (Motsch.) adults from two host plants (Populus simonii × P. pyramidliscr cv. Opera Hsu. and Salix matsudana Koidz) fed on three different host tree species (Acer negundo Linn., S. matsudana Koidz and P. simonii × P. pyramidliscr cv. Opera Hsu.) were investigated. Enzyme activities of endoglucanase and β-glucosidase in the intestines of the insects were measured. The results show that there are no statistically significant differences in the enzyme activities of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 20 publications
(13 reference statements)
1
1
0
Order By: Relevance
“…pyramidalis , characterized by strong resistance, lignocellulose enzyme activity was lowest ( Figure 2 ). This result is consistent with previous studies by Geib et al (2010) and Li et al (2010) . In addition, Chen et al (2006) concluded that the order of cellulase activities in the guts of A. glabripennis larvae was β-1,4-glucosidase > β-1,4-endoglucanase > β-1,4-exoglucanase, consistent with our current results.…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…pyramidalis , characterized by strong resistance, lignocellulose enzyme activity was lowest ( Figure 2 ). This result is consistent with previous studies by Geib et al (2010) and Li et al (2010) . In addition, Chen et al (2006) concluded that the order of cellulase activities in the guts of A. glabripennis larvae was β-1,4-glucosidase > β-1,4-endoglucanase > β-1,4-exoglucanase, consistent with our current results.…”
Section: Discussionsupporting
confidence: 94%
“…For β-exoglucanase activity, 200 μL of a 1% avicel solution was combined with 100 μL of crude gut extract ( Kukor et al, 1988 ). For β-glucosidase activity, 200 μL of a 1% salicin solution was combined with 100 μL of diluted enzyme solution (crude gut extract diluted five times with acetic acid-sodium acetate buffer) ( Li et al, 2010 ). For β-endoglucanase activity, 200 μL of 1% carboxymethylcellulose solution was combined with 100 μL of diluted enzyme solution ( Kukor et al, 1988 ).…”
Section: Methodsmentioning
confidence: 99%